Pengaruh Terapi Nebulizer dan Pursed Lip Breathing terhadap Penatalaksanaan Asma di Instalasi Gawat Darurat RSUD Temanggung - Puspita Dewi, Kessi Anggraeni; Khoriyati, Azizah; Priyo Krisyanto, Widayat (An Idea Health Journal, 2025)
Background:Asthma is a chronic respiratory disorder marked by airway inflammation, narrowing, edema, and excessive mucus production, resulting in impaired ventilation and ineffective airway clearance. Effective interventions are essential to alleviate symptoms and optimize respiratory function. Nebulizer therapy and pursed-lip breathing are widely employed to manage asthma symptoms; however, the synergistic impact of these two modalities remains underexplored.Methods:This case study involved a patient with a clinical diagnosis of asthma presenting with acute shortness of breath. The intervention protocol consisted of 10 minutes of nebulizer therapy followed by 5 minutes of pursed-lip breathing. Clinical parameters oxygen saturation (SpO?), respiratory rate, heart rate, sputum consistency, adventitious breath sounds, and dyspnea scale were measured before and after the intervention.Results and Discussion: Post-intervention assessment revealed notable clinical improvements. Oxygen saturation increased from 89% to 96%, respiratory rate declined from 37 to 24 breaths per minute, and heart rate decreased from 127 to 98 beats per minute. Additionally, sputum consistency became thinner, adventitious sounds such as wheezing and rhonchi subsided, and the dyspnea scale improved from level 2 (moderate) to level 0 (normal). These findings suggest that the combined application of nebulizer therapy and pursed-lip breathing enhances airway patency, reduces respiratory distress, and improves ventilation. Conclusion: The combined use of nebulizer therapy and pursed-lip breathing technique proved effective in improving airway clearance and respiratory function in an asthma patient, indicating potential for broader clinical application in acute asthma care.